If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = -1x + -7 Reorder the terms: 5 + 3x = -1x + -7 Reorder the terms: 5 + 3x = -7 + -1x Solving 5 + 3x = -7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 5 + 3x + x = -7 + -1x + x Combine like terms: 3x + x = 4x 5 + 4x = -7 + -1x + x Combine like terms: -1x + x = 0 5 + 4x = -7 + 0 5 + 4x = -7 Add '-5' to each side of the equation. 5 + -5 + 4x = -7 + -5 Combine like terms: 5 + -5 = 0 0 + 4x = -7 + -5 4x = -7 + -5 Combine like terms: -7 + -5 = -12 4x = -12 Divide each side by '4'. x = -3 Simplifying x = -3
| y^2-2y+1=64 | | Y=Go+d | | 800+160-30=0 | | 2(x+20)=2(x-10) | | 5/6x=-218 | | 7/5x=3/10 | | (x)(x-2)=35 | | Sin^2(X)=2cosx | | 800(100+30)=0 | | 102=(x+18)+(x-12)+x | | -x+13=x+6 | | 21d=-63 | | 56x=-218 | | M=57 | | -5y+10x=-15 | | 168=-6(8x-4) | | 4p(p+2)=0 | | 665/7 | | 4(n-3)=28 | | -3(-3+5x)=-6 | | -7(2x-6)=154 | | -9x+5x=16 | | 6(-3+2b)=-90 | | V=pir^2h2/3 | | -5(-7+3x)=-70 | | x(800+x)x(100+30)= | | 625=3.14(r^2) | | -123=-3(7x-8) | | -6(x+1)-13=21+8 | | 92=-4(7a-2) | | 6(3r-2)-6=-90 | | 7x^2-14x+7=0equation |